On the relation between oral contraceptive use and self-control - Smith, Alyssa C.; Smilek, Daniel (Frontiers in Endocrinology, 2024)
In two studies we examined the relation between oral contraceptive (OC) use and selfreported levels of self-control in undergraduate women using OCs (Study 1: OC group N = 399, Study 2: OC group N = 288) and naturally cycling women not using any form of hormonal contraceptives (Study 1: Non-OC group N = 964, Study 2: Non-OC group N = 997). We assessed the self-overriding aspect of self-control using the Brief Self-Control Scale (BSCS) and strategies for self-regulation using the Regulatory Mode Scale (RMS), which separately measures the tendency to assess one's progress towards a goal (assessment), and the tendency to engage in activities that move one towards an end goal (locomotion). In Study 1, we found no significant differences between OC and non-OC groups in their levels of self-overriding or self-regulatory assessment. However, we found that those in the OC group reported significantly greater levels of self-regulatory locomotion compared to those in the non-OC group, even after controlling for depression symptoms and the semester of data collection. The findings from Study 2 replicated the findings from Study 1 in a different sample of participants, with the exception that OC use was also related to higher levels of assessment in Study 2. These results indicate that OC use is related to increases in self-regulatory actions in service of goal pursuit and perhaps the tendency to evaluate progress towards goals.